PENGARUH INTEGRITAS DAN LOYALITAS TERHADAP KEBIJAKAN PIMPINAN DI PT ASDA PERKEBUNAN AEK BURU SELATAN - Sri Ayla; suci widya prastika (Jurnal Mantik, 2022)
This study aims to determine and analyze the effect of partial integrity and loyalty on leadership policies at PT. South Aek Buru Plantation Asda. The population in this study were employees of PT. South Aek Buru Plantation Asda, totaling 78 employees, its mean population as a sample. The collecting data used questionnair and observations. The research method used is descriptive analysis method, classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination test (R2). Based on the assurance coefficient test, it shows that R square 0.949 indicates that about 94.9% of the variation in the reliable variable (approach) can be explained by honor and devotion factors and the remaining 5.1% is affected. Based on the results of the fractional test (t test), this tends to be reasonable that honesty has no significant effect on the initiative approach because the value of tcount (1.170)> table (1.991) is 0.245 <0.05. Meanwhile, persistence affects the authority's strategy because the value of tcount (38.021)> table (1.991) with a large value of 0.000 <0.05. Considering the consequences of the F test, it tends to be concluded that the honor and reliability factors together significantly affect the regulatory authority.